2013
DOI: 10.1167/13.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Object-based saccadic selection during scene perception: Evidence from viewing position effects

Abstract: The goal of the present study was to further test the hypothesis that objects are important units of saccade targeting and, by inference, attentional selection in real-world scene perception. To this end, we investigated where people fixate within objects embedded in natural scenes. Previously, we reported a preferred viewing location (PVL) close to the center of objects (Nuthmann & Henderson, 2010). Here, we qualify this basic finding by showing that the PVL is affected by object size and the distance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 48 publications
4
71
0
Order By: Relevance
“…During these refixations, the eyes showed no systematic bias towards either side of the object. This is consistent with Pajak and Nuthmann's (2013) findings for objects in natural scenes. They observed that refixations launched from object boundaries bring the eyes closed to the object's center, whereas refixations that are launched from the center keep the eyes close to the center.…”
Section: Landing Positions Of Refixationssupporting
confidence: 92%
See 4 more Smart Citations
“…During these refixations, the eyes showed no systematic bias towards either side of the object. This is consistent with Pajak and Nuthmann's (2013) findings for objects in natural scenes. They observed that refixations launched from object boundaries bring the eyes closed to the object's center, whereas refixations that are launched from the center keep the eyes close to the center.…”
Section: Landing Positions Of Refixationssupporting
confidence: 92%
“…Fixations were longer towards the center of isolated words and objects, which is in line with previous reports on word identification (Vitu et al, 2007), sentence reading (Hyönä & Bertram, 2011;Nuthmann et al, 2005Nuthmann et al, , 2007Vitu et al, 2001), object recognition (Henderson, 1993) and scene viewing (Pajak & Nuthmann, 2013). This effect, referred to as the inverted OVP (I-OVP) effect, might appear counterintuitive when assuming that fixation duration is an index of processing difficulty.…”
Section: All Viewing-position Effects Generalize To Object Viewingsupporting
confidence: 90%
See 3 more Smart Citations